Barriers and Bootstraps? The Role of Attributions for Social Mobility Success and Failure in Policy Support and Faith in the American Dream - Shanahan, Erin; Wilson, Anne E. (Journal of applied social psychology, 2025)
ABSTRACT Despite rising inequality making upward social mobility difficult, faith in the American Dream persists. Americans are often exposed to narratives where hard work leads to upward social mobility but are less likely to hear about the numerous instances where the same efforts don't pay off. Across three pre‐registered studies, we examined responses to identical narratives of social mobility effort that either ended in success or failure. Despite equal efforts, a target was viewed as less hardworking and competent and worse at managing their time and money when they failed versus succeeded to be upwardly mobile. Liberals and conservatives made equally strong internal explanations for social mobility successes. However, conservatives explained failures with more internal and less societal attributions than liberals. These attributions were found to have important implications for faith in the American Dream and support for policies to promote equality. Moreover, experimentally inducing a focus on societal barriers to upward mobility (vs. internal factors) increased support for policies to reduce these barriers, and reduced faith in the American Dream, particularly among conservatives.